Alliance Experience, IT-Enabled Knowledge Integration, and Ex Ante Value Gains - Liu, Yu; Ravichandran, T. (Organization Science, 2015)
An important theme in the alliance research has been the study of how prior alliance experience translates into value gains from alliances. Despite the strong theoretical argument regarding the value-enhancing role of alliance experience, past research has reported mixed results. In an attempt to resolve the inconclusive findings, we provide a more fine-grained view of alliance experience by examining characteristics such as relatedness and diversity, which are defined based on the functional focus and the industry of the partner. Furthermore, we argue that since leveraging alliance experience is a learning process, a firm’s knowledge integration capabilities enabled by information technology (IT) should influence the extent to which the firm benefits from alliance experience. Using data from 1,030 alliances made by 89 firms across 11 industries, we test the effects of relatedness and diversity on abnormal returns following alliance announcements. We find that functionally related experience is positively related to abnormal returns, whereas partner industry-based related experience affects the expected value negatively. We also find that a firm’s IT-enabled knowledge integration positively moderates the effects of both related and diverse experience on abnormal returns. Our findings highlight that although knowledge gained through prior experience is important, complementary capabilities that enable firms to leverage and utilize such knowledge are also necessary for ex ante value creation in alliances. We interpret these findings and discuss their implications for research in both strategic management and information systems.